2006
DOI: 10.1111/j.1469-1809.2006.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variations in TP53 Mutational Spectrum in Ovarian Carcinomas

Abstract: SummaryThe TP53 gene mutational spectrum in human tumours shows variations related to tissue of origin, carcinogen exposure or molecular background. We have compared TP53 mutations in ovarian carcinomas from different geographical regions; this study was based on data extracted and verified from the IARC database (R10, 2005), and on our results from 127 carcinomas. In total 873 mutations were evaluated. Tumours from Japan and Korea had a higher frequency of exon 7 mutations (38% vs 25%, p = 0.011) and lower fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
1
26
0
1
Order By: Relevance
“…In contrast, HG serous carcinomas often present in advanced stages (stages III-IV) and rarely harbor mutations in KRAS/BRAF/ERBB2 . HG serous carcinomas grow rapidly and are highly aggressive and over than 75% of these tumors harbor TP53 mutations (1418). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HG serous carcinomas often present in advanced stages (stages III-IV) and rarely harbor mutations in KRAS/BRAF/ERBB2 . HG serous carcinomas grow rapidly and are highly aggressive and over than 75% of these tumors harbor TP53 mutations (1418). …”
Section: Introductionmentioning
confidence: 99%
“…This has been shown in ovarian (high nuclear survivin in the TP53 mutant tumours), pancreatic, breast and gastric carcinomas [54-57]. We have failed to observe this correlation in our large group of 435 tumours; however, we evaluated TP53 accumulation only and it occurs with a frequency approximately 30% lower than TP53 mutations, thus the rate of TP53 dysfunctional tumours in our group may be much higher [33]. …”
Section: Discussionmentioning
confidence: 68%
“…Biotinylated secondary goat anti-rabbit IgG (for survivin) (1/1500) and anti-mouse IgG (for TP53) (1/1500), peroxidase-conjugated streptavidin (1/500) (all from Immunotech, Marseille, France), and DAB were used as a detection system. As a positive control for TP53 accumulation, we used a tumour with a defined TP53 gene missense mutation [33]. Normal rabbit IgG or normal mouse IgG of the same subclasses and at the concentrations of the relevant primary antibodies served as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, abnormalities within TP53 (which are common in ovarian cancer [36]) may disturb the normal physiological function of CEBPA and change the way it affects ovarian cancer development and prognosis. As a confirmation of this hypothesis, Seipel et al [37] have recently shown that restoring the TP53 function after treatment with cytotoxic chemotherapy compounds and TP53 restoring non-genotoxic agents induced CEBPA gene expression, myeloid differentiation, and cell-cycle arrest in AML cells.…”
Section: Discussionmentioning
confidence: 99%